Engineering and Biotechnology for Society - Marroquín-De Jesús, Ángel; Castillo Martínez- Luz Carmen; Alonso-Arroyo, Juana; Cruz-Carpio, Luis Eduardo (ECORFAN-Mexico, 2024)
The importance of the study of times and movements in the various industries lies in explaining that the work is organised according to the main techniques of work measurement; time study with stopwatch, work sampling and predetermined time standards. Through the application of quality tools, it is determined which areas of work represent a problem in production in order to have a better performance, efficiency, effectiveness and improvement of the operators for the realisation of certain processes. Such is the case of the flower sector in the municipality of Villa Guerrero, Mexico, where demand is seasonal, which means that companies dedicated to the production of roses on a large scale do not have an adequate organisation in various processes, causing inefficiency and a series of delays in production. Therefore, the importance of this research work lies in carrying out a time and motion study to eliminate slack time and eliminate unnecessary elements that could affect productivity, safety and quality of production in the company Flor de María, where it was hypothesised that the time and motion study will help the company Flores de María to improve the working methods of the packaging process in the activities of rehydration, calibration, stem selection, labelling (Kanban) in this area to increase the efficiency of the production process.